Engineering the Metaverse for Innovating the Electronic Business: A Socio-technological Perspective - Festa, Giuseppe; Melanthiou, Yioula; Meriano, Pina (My University, 2022)
The metaverse is a hybrid world, mixing real, augmented, and virtual spaces, in which people (as users) can be represented in a three-dimensional way, with an avatar, activating services, interacting with other users/avatars, and exploiting/exploring innovative experiences. The difference with other virtual reality worlds as known so far is essentially the feeling of living spaces with other avatars, with almost infinite possible applications, through immersive access, emersive configurations, and continuous interactions among real, augmented, and virtual dimensions. Several companies have been trying to explore the metaverse for their business, and naturally, Facebook/Meta most of all. This study proposes an analysis about definition, conceptualisation, and activation, from a socio-technological point of view, of the metaverse, providing a SWOT analysis for its evaluation in a business perspective.
Keywords: Business; Technology